An Etruscan empire in the Mediterranean world. Antiquities, cultural models and national identities in 18th-century Italy - Antonino de Francesco (Diciottesimo Secolo)
The essay revisits the figure of the Scotsman James Byres, son of a Jacobite at the exiled court of the Stuart pretender, who gained renown in Rome as a cicerone for English travelers in Italy. In particular, the study sheds new light on the journey undertaken in 1767 with Roger Wilbraham to southern Italy. Rather than being a traditional educational tour, this itinerary sought to substantiate the hypotheses of Tuscan antiquarians, which proposed the existence of an Etruscan empire spanning the entire Mediterranean before its memory was obscured by the ascendancy of Rome. Byres aimed to demonstrate the existence of an Etruscan civilization that served as the foundation of ancient Roman culture. However, the triumph of Winckelmann – who regarded Etruscan studies with disdain – marked the end of this alternative interpretation of antiquity. Consequently, the myth of an Etruscan Italy was subsumed within the nationalist discourse of the early 19th century.